(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2024)
This article addresses the phenomenon of indigenous arts through a multidisciplinary literature and a brief analysis of three artistic works by Barbara Kariri, Juão Nyn e Iris e Iara Campos. We discuss how art has been a reclaimed space, subverting the senses of coloniality (Quijano, 2005) that constitutes the institutionalized artistic field (Meireles, 2020). Based on the notion of body-territory, we reflect upon indigenous paths of indigenous arts, acknowledging its elements and cosmoperceptions (Martins, 2021).